FAIRNESS OF HUMAN RESOURCE MANAGEMENT PRACTICES, LEADER-MEMBER EXCHANGE AND ORGANIZATIONAL COMMITMENT - Daisy Kee Mui Hung; Mahfooz A. Ansari; Rehana Aafaqi (Asian Academy of Management Journal, 2004)
The purpose of this research was to test the hypothesis that relations between fairness perception of human resource management (HRM) practices and organizational commitment are affected by the quality of leader-member exchange (LMX). Specifically, we predicted the unique (positive) contribution of fairness perception of HRM practices and LMX as well as their interaction to organizational commitment. A sample of 224 managers was drawn from nine diverse multinational, manufacturing companies located in Northern Malaysia. Participation in the research was voluntary. Data were gathered by means of a survey questionnaire that consisted of a series of psychometrically sound scales to assess the employed variables in the study. Hierarchical multiple regression results provided support for the direct impact of fairness perceptions and LMX on each component of commitment. But significant interactions were convincingly evident only in the case of affective commitment. These interactions suggest that the impact of fairness perceptions of HRM practices on affective commitment is not unconditional. Key implications of the survey findings both for theory and practice are discussed, potential limitations are specified, and directions for future research are suggested.